Um estudo sobre o pronome Vos na fala de professores universitários paraguaios em situação de sala de aula - Quintana, Francisco Alcidez Candia (2007)
This investigation is a study of the personal pronouns TÚ, VOS y USTED in Paraguayan Spanish and aims to verify the reach of the VOS pronoun, a variant of the second person of the singular used in Paraguayan Spanish, instead of TÚ, an informal personal pronoun, and USTED, a formal personal pronoun, both registered in Spanish normative grammar. The work is based in the speech of nine Paraguayan subjects, university professors, four of them male and five female, with age from 29 to 51 years, all doctors, masters or specialists in different areas. Data was colleted from audio recordings of classes given by the teachers, a situation taken as formal. The option for subjects having graduate degrees and members of high middle-class obeyed to a sociolinguistic rule according to which changes in language take more time to arrive at social classes with a greater spending power and more formal schooling, as well as to more aged people and men. The speech of subjects with this profile comes to be monitored by normative grammar, which also determines more conservative linguistic uses. In addition, these uses have a greater probability of happening in formal situations. Thus, the work is inserted in two linguistics trends: (1) Sociolinguistics, that is to say, the study of the spoken, observed language, deciphered and analyzed within a social context, and (2) Pragmatics, that is to say, the study of language in relation to who one speaks with, who one speaks to and where one speaks. With this aim in view, two types of analysis were done: a quantitative one, checking the instances of the three pronouns in the corpus recordings, and a qualitative, which describes situations of use of those pronouns during the classes. The results showed that: in the first place, the use of VOS for the second person of the singular is heavily present in the speech of Paraguayan university professors in the classroom, followed by USTED, whereas TÚ has only two instances. Secondly, the qualitative analysis of statements or pieces of statements of the different teachers, about different topics and different class situations, pointed to a polarity between not only situations of formality and informality in the personal relationships between teachers and students, but also in direct speech, when the teacher brought to light fake situations of relationship between hierarchically different people as regards function in social terms. Also the degree of face exposing of one of the teachers showed the passage from the registry of VOS to the one of USTED